(untitled) (mathematica didactica, 2005)
Students formulating mathematical tasks is a rarely used method in secondary education. This is quite surprising because this method can be easily and effectively integrated into maths lessons especially as we are interested in the transformation between reallife situations and mathematical models. This article aims to promote the method of formulating tasks. This method is an example of a particular type of open exercise. Thereby, the cognitive demand for students is quite the opposite to the usual way of mathematical work. To show a possible spectrum of formulating tasks we hand out examples from the field of subtraction and division of fractions in grade 6.